Переработка фосфогипса в полугидрат сульфата кальция - Винниченко, Варвара Ивановна; Супряга, Наталия Николаевна (НТУ "ХПИ", 2016)
Проведен обзор и сделаны выводы о повышенной энергоемкости существующих машин для производства строительного гипса. Обоснована целесообразность применения обжига материала в тонкодисперсном состоянии. Представлены результаты проведенного обжига фосфогипса во взвешенном состоянии помольно-обжиговой установке. Установлено, что качество полученного из фосфогипса строительного гипса соответствует требованиям существующих стандартов, а время обжига сокращается на несколько порядков по сравнению с применяемыми в настоящее время машинами. Полученное вяжущее можно применять для получения широкой номенклатуры строительных материалов и изделий.

Presented a study on recycling gypsum-containing waste tonnage production of fertilizers and phosphoric acid – phosphogypsum. A review of existing production lines and systems for the processing of phosphogypsum in stucco, in particular machines for his firing. The conclusions of the environmental inappropriate and loss of production due to the increased power consumption. Expediency of firing the material in a finely divided state. The results of the firing phosphogypsum suspended on established Entirely-roasting plant. It is found that the quality of the obtained phosphogypsum plaster comply with existing standards, and the firing time is reduced by several orders of magnitude compared to currently used machines. The resulting binder may be used to produce a wide range of gypsum building materials and products. The developed equipment makes it possible not only to obtain high-quality building materials, but also to solve the environmental problem of disposal tonnage phosphogypsum dumps and thereby free up vast tracts of land designated for the production of waste.
Processing of phosphogypsum in hemi-calcium sulfate
Keywords: фосфогипс; гипс строительный; обжиг; взвешенное состояние; энергоемкость; металлоемкость; пониженный расход топлива; гипсоварочный котел; вращающийся барабан; автоклав; phosphogypsum; gypsum plaster; firing in suspension; power consumption; metal consumption; lower fuel consumption